Exercise-induced laryngeal obstruction (EILO) in athletes: a narrative review by a subgroup of the IOC Consensus on 'acute respiratory illness in the athlete'. Issue 11 (22nd February 2022) - Clemm, Hege Havstad; Olin, J Tod; McIntosh, Cameron; Schwellnus, Martin; Sewry, Nicola; Hull, James H; Halvorsen, Thomas
Abstract : Exercise-induced laryngeal obstruction (EILO) is caused by paradoxical inspiratory adduction of laryngeal structures during exercise. EILO is an important cause of upper airway dysfunction in young individuals and athletes, can impair exercise performance and mimic lower airway dysfunction, such as asthma and/or exercise-induced bronchoconstriction. Over the past two decades, there has been considerable progress in the recognition and assessment of EILO in sports medicine. EILO is a highly prevalent cause of unexplained dyspnoea and wheeze in athletes. The preferred diagnostic approach is continuous visualisation of the larynx (via laryngoscopy) during high-intensity exercise. Recent data suggest that EILO consists of different subtypes, possibly caused via different mechanisms. Several therapeutic interventions for EILO are now in widespread use, but to date, no randomised clinical trials have been performed to assess their efficacy or inform robust management strategies. The aim of this review is to provide a state-of-the-art overview of EILO and guidance for clinicians evaluating and treating suspected cases of EILO in athletes. Specifically, this review examines the pathophysiology of EILO, outlines a diagnostic approach and presents current therapeutic algorithms. The key unmet needs and future priorities for research in this area are also covered.